The Relationship Between E-Service Quality And E-Satisfication - McGuire, Stephen J. J.; Rosary, Juao C. Costa (Journal of Management, 2022)
This study's goal is to examine the relationship between e-service quality and e-satisfaction, e-trust and e-satisfaction, e-service quality and e-customer loyalty, e-satisfaction and e-customer loyalty, indirect effects of e-service quality on e-customer loyalty through e-satisfaction, and significant indirect effects of e-trust on e-customer loyalty through e-sa The research method is quantitative, and the purposive sampling approach is a non-probability sampling strategy. 301 online shop customers who had made purchases there served as the study's respondents. Through the use of social media, online questionnaires were sent to gather research data. employing SmsrtPLS 4.0 software tools for structural equation modeling (SEM) analysis of research data. Validity, reliability, and hypothesis testing (significance) are the phases of data analysis. According to the study's findings, e-service quality has a direct, positive, and considerable impact on e-satisfaction. The impact of e-Trust on e-Satisfaction is immediate, positive, and large. There is a strong positive and significant direct effect of e-service quality on e-customer loyalty, as well as a positive effect and direct significance of e-trust on e-customer loyalty. Additionally, there is a strong and significant positive indirect effect of e-service quality on e-customer loyalty through e-satisfaction, and there is a strong and significant positive indirect effect of e-Trust on e-customer loyalty.